IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS PENDEKATAN SAINTIFIK DI ERA PANDEMI COVID-19 (STUDI KASUS SMP ISLAM AL-AKBAR SINGOSARI) - Dewi Isroiyah; Dwi Fitri Wiyono; Indhra Mustofa (VICRATINA, 2022)
PAI learning which tends to use the lecture method is considered to cause student saturation in learning. The implementation of the 2013 curriculum, the scientific approach was chosen by the teacher so that students are more active and critical in learning. In reality, it has not run optimally because the level of student activity is still low, each step of learning has not been maximized, the facilities are inadequate, not all PAI materials can be applied using a scientific approach. This study aims to describe the concept of learning, the steps of learning, as well as the advantages and disadvantages of PAI learning based on a scientific approach at SMP Islam al-Akbar Singosari. The results showed that the learning concept was implemented in three activities including planning, implementation, and assessment. The learning steps are carried out with five steps of a scientific approach including observing, asking, trying, association, and communication. The advantages are that the material can be completed in a short time, students can study in groups, are more active, can explore student creativity, teachers can easily assess students, knowledge can last longer and understand more, learning is more interactive, interesting and meaningful, and improves student achievement. The drawbacks are that it requires inadequate media, facilities and infrastructure, takes a long time, students' psychology, and not all PAI materials are compatible with the scientific approach.